Implementación de un sistema web para la gestión de la información del departamento de vinculación de la Universidad Técnica de Cotopaxi extensión La Maná periodo octubre 2014 – febrero 2015 - Alcaciega Guanín, Jorge René (2016)
Today is very important to preserve the information from the institutions, this thesis project involves the implementation of a Web System for Information Management in the Department of Linking Cotopaxi Technical University La Maná, which will allow the coordinator of the body managing the documentation generated daily, the information will be digitized and stored in the system to be implemented.